Highly Enantioselective Three-Component Direct Mannich Reactions of Unfunctionalized Ketones Catalyzed by Bifunctional Organocatalysts - Guo, Qunsheng (2013)
[Image: see text] A highly stereoselective three-component direct Mannich reaction between aromatic aldehydes, p-toluenesulfonamide, and unfunctionalized ketones was achieved through an enolate mechanism for the first time with a bifunctional quinidine thiourea catalyst. The corresponding N-tosylated β-aminoketones were obtained in high yields and excellent diastereo- and enantioselectivities (up to >99:1 dr and >99% ee).